2002
DOI: 10.1093/clinchem/48.2.255
|View full text |Cite
|
Sign up to set email alerts
|

European Concerted Action on Anticoagulation. Use of Plasma Samples to Derive International Sensitivity Index for Whole-Blood Prothrombin Time Monitors

Abstract: Background: To simplify International Sensitivity Index (ISI) calibration, the possibility of substituting fresh plasma for fresh whole-blood samples with point-of-care testing (POCT) whole-blood monitors was investigated in a three-center study of three different POCT systems. Methods: A modified full WHO calibration procedure based on 20 healthy controls and 60 coumarin-treated patients was performed on three monitoring systems with whole-blood and plasma samples against plasma tested using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…It is the ISI value that can be calibrated. It is possible to calibrate CoaguChek with whole blood, fresh, citrated plasma [77–79], and even lyophilized plasma [80].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the ISI value that can be calibrated. It is possible to calibrate CoaguChek with whole blood, fresh, citrated plasma [77–79], and even lyophilized plasma [80].…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that calibration of the POCT coagulometers should and could be performed [4,78,79,96] in order to provide accurate INR measurements [83]. Although possible, this does not seem feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Serum and citrated (3.2%; BD Vacutainer, Franklin Lakes, NJ) plasma samples were obtained from the same three donors. Citrated plasma (100 μl) was mixed 1:1 with VBS ++ buffer supplemented to 16.3 mM calcium chloride to induce coagulation as described (Poller et al, 2002). Serum and coagulated plasma samples were allowed to clot overnight at 4°C.…”
Section: Plasma Preparationmentioning
confidence: 99%
“…In some POCT systems, it is possible to use recalcified citrated plasma substituting whole blood for ISI assignment. 54 In the same way, recalcified plasma can be used for quality control of these POCT systems. It should be noted, however, that recalcified plasma cannot be used in all POCT systems, for example, those based on reflection of light by erythrocytes.…”
Section: Poct Quality Controlmentioning
confidence: 99%